THE CHRISTIANISATION OF ANCIENT MOTIFS IN HISTORYJA WOJNY MIĘDZY POMPEJUSZEM I JULIJUSZEM (IN THE LIGHT OF FATHER TOMASZ NARGIELEWICZ’S WRITING STRATEGIES) - Gacka, Dorota (Prace Polonistyczne, 2021)
This article is divided into two parts. The first – historical and literary – part offers information about a baroque Dominican writer, Tomasz Nargielewicz (d. 1700), and about a Latin writer, Lucan, whose epic poem Pharsalia was translated into Polish prose by Nargielewicz, who entitled it Historyja wojny między Pompejuszem i Julijuszem (The History of the War between Pompey and Julius). His work is not a faithful translation, but a strong paraphrase, as Nargielewicz omits, elaborates, and rearranges many fragments of the original poem. Due to the fact that he was a Dominican, Nargielewicz added Christian elements to the text. Furthermore, this part of the article will also address the question of whether in his work Nargielewicz made use of the translations of Lucan’s poem by two other baroque poets, John Alan Bardziński and Adalbertus Stanislaus Chrościński. The second – analytical and editorial – part of the article presents excerpts from Nargielewicz’s work, which has never been transcribed before, such as the one that describes Cato the Younger and fragments containing speeches. The speakers who deliver them are: Vulteius (the captain of a Roman ship), Cato (in the temple of Ammon), Achoreus (at a feast at the court of Ptolemy Dionysus), and Cleopatra (at the time of death). The article also presents the final part of the text, where the Christian flavour is most evident.